자율주행 모빌리티 기반의 가변형 시트에 관한 연구 -L5 자율주행 자동차를 중심으로 - 정상헌; Sangheon Chung; 노승일; Seung Il Lo (기초조형학연구, 2021)
현재 모빌리티에서 가장 중요한 요소 중 하나로 자리 잡은 실내 공간의 거주성은 자율주행 기술의 발전에 따라 변하기 시작했다. 완벽한 자율주행 기술을 구현하는 것은 현재로서 불가능하지만, 자동차업체들의 치열한 경쟁으로 인해 근미래 기술 구현의 가능성을 보이면서 효율적이면서도 인테리어의 거주성을 향상한 모빌리티들이 소비자들에게 선보여지고 있으며, 소비자들이 실내 공간에서 현재와는 차원이 다른 활동을 할 수 있다는 다양한 가능성을 제시하고 있다. 최근 출시되고 있는 모빌리티의 실내 공간은 소비자들을 위한 거주성이 강조된 공간으로 변화하고 있고, 시간이 흐르면서 실내의 구조와 시트의 중요성은 더욱 확장될 것이므로 미래 모빌리티를 위한 인테리어 구조, 그리고 시트에 관한 연구가 필요하다. 그러므로 다양한 시트들의 분석을 진행하고 가상 소비자를 설정한 후, 가변형 시트를 통해 자율주행 모빌리티 실내 공간의 효율성을 향상하고 소비자의 요구사항을 만족하게 할 수 있는 가변형 시트 디자인 제안을 목적으로 한다. 연구 방법과 과정은 모빌리티의 인테리어 또는 시트에 관한 논문자료들과 현실적인 실내 구조, 그리고 설정한 가상 소비자들을 위한 적합한 시트의 기능들에 대해 알아보기 위하여 양산형 운송기기. 자동차나 비행기들의 시트, 최신 컨셉 자동차의 인테리어 그리고 주거용 가변형 가구들을 분석하였다. 다양한 시트들의 기능, 사용된 재질 그리고 자율주행 모빌리티와 가상 소비자의 관점에서 장단점을 분석하고 표로 도출하여 가변형 시트 디자인 컨셉의 기반을 마련하였다. 분석을 통해 도출한 기능, 재질, 그리고 장점들을 바탕으로 자율주행 모빌리티의 실내 구조와 가변형 시트 디자인을 진행하였고, 가변형 시트의 스타일링과 수집된 기능, 재질, 그리고 장점들을 접목하여 실내 공간의 효율성을 살리고 가상 소비자들의 요구사항을 충족시키는 가변형 시트 디자인을 제안하였다. The habitability of indoor space, which is currently one of the most important factors in mobility, has begun to change with the development of autonomous driving technologies. Although it is currently impossible to implement a complete self-driving technology, the fierce competition of automobile brands has shown consumers the possibility of implementing technology in the near future, providing consumers with more efficient and more residential mobility. The recently released interior space of mobility is changing to a space with an emphasis on habitability for consumers, and the importance of interior structures and seats will expand over time, requiring research into interior structure and seats for future self-driving mobility. Therefore, the purpose of this project is to propose a transformable seat design that can improve the efficiency of self-driving mobility interior space and satisfy consumers' requirements or needs through transformable seats after conducting an analysis of various seats and setting up virtual consumers. As research methods and processes, thesis data related to mobility's interior and seats were looked over to consider interior spaces and seats related to the virtual consumers. Also, the example of seats of cars, airplanes, the interior of the latest concept cars, and transformable furniture for housing were analyzed to refer to realistic interior structures and seat functions that could satisfy the consumer needs. The functions of various seats, materials used, and advantages and disadvantages from the perspective of self-driving autonomous mobility and virtual consumers were analyzed and tabulated to lay the foundation for a transformable seat design concept. Based on functions, materials, and advantages derived from the analysis, the interior structure of self-driving mobility and transformable seat design was developed, combining the styling of transformable seats with the collected functions, materials, and advantages to enhance the efficiency of indoor space and meet the needs of virtual consumers.